From poop to prep - Using rabbit poop as an organic fertilizer for your garden / Noor Azli Affendy Lee - Affendy Lee, Noor Azli (Academy of Language Studies, 2022)
In July 2021, I decided to get myself a male and two female New Zealand white rabbits in order to experience rearing rabbits for meat. Even after reading numerous information and guides on rabbit care and breeding, I did not expect having them inside my house to be very challenging in two ways - they eat a lot and they poop a lot too, at least more than what I expected! According to Faraday (2020), a single rabbit can deposit 200 to 300 poops in a day, and I had three of them! Apart from the problem of maintaining cleanliness of their enclosure, I also had to figure out what to do with their poops. Rabbit poop is pretty straightforward - what they eat goes in, the poops come out! They eat a completely plant-based diet consisting of hays, vegetables and specially- designed rabbit pallets, which were getting pricier in the current Covid-19 pandemic economy.